Surveillance of Drug Residue Profiles in Gallus gallus domesticus (Silkie Chickens) in Taiwan - Chiao-Hsu Ke; Jr-Wei Chen; Chen-Si Lin (Animals)
Veterinary drugs are extensively utilized in poultry farming for purposes such as disease prevention, disease treatment, and feed efficiency enhancement. However, the application of these drugs can lead to unacceptable residues in edible products. This study aimed to investigate the residue profiles of veterinary drugs in silkie chickens. A total of 130 chicken samples were collected from two major retail markets in Taiwan between 2022 and 2024. The analysis of drug residues was conducted using liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS). The overall detection rate of drug residues was 57.7%, and most of these residues were found to be below the maximum residue limits. Among the detected drugs, trimethoprim was the most prevalent, followed by nicarbazin, robenidine, decoquinate, diclazuril, and sulfamonomethoxine. Notably, there was a 31.4% chance that different samples from the same flock would yield varying results. Furthermore, a positive correlation was observed between drug residues and sample weight. In conclusion, this study provides valuable epidemiological data on drug residue profiles in silkie chickens in Taiwan. In the future, it is highly recommended that veterinary drug residues be continuously monitored, and food product sampling protocols be adjusted annually to ensure ongoing compliance with safety standards and protect consumer health.